PENERAPAN MULTISISTEM SILVIKULTUR PADA UNIT PENGELOLAAN HUTAN PRODUKSI : TINJAUAN ASPEK EKOLOGI - Cecep Kusmana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Forest is a renewable resources having various benefits including products, environmental services and beautifulness of landscape. Therefore, forest must be managed using sustainable based principle to produce sustainably the maximum benefit. Howevere, the practices of forest management by the companies of forest Concession have created the various qualities of Logged Over Area (LOA). According to the landscape point of view, LOA were composed of mosaics with various qualities of lands and stands having low productivity. Based on this fenomena, LOA had betters to manage by a silviculture multisystem incording with local biophysical properties. This silviculture system should be implemented to improve the land productivity through minimizing soil disturbances, maintaining the supply of soil organic matters and biodiversity. Beside woods and by forest products, emphirically forest ecosystem has an importan role in water preservation, CO2 sequestration, and carbon storage. Keywords: Logged Over Area, Production Forest, Silviculture Multisystem